Electronic structure of Gd based transition metal antimonides GdTSb (T = Ni, Pt) - Sahariya, Jagrati; Kumar, Pancham; Bhamu, K. C.; Soni, Amit (2nd International Conference on Condensed Matter and Applied Physics (ICC-2017), 2018)
We report the electronic and magnetic properties of ternary GdNiSb and GdPtSb compounds with cubic MgAgAs type structure. The energy bands, density of states and atom specific magnetic moments of compounds have been computed using GGA+U approach. The calculations predict that GdNiSb is a small band gap semiconductor whereas GdPtSb is metallic in nature.

Opto-electronic analysis of Cs2PdCl2Br4 Perovskites compounds for photovoltaic applications - Soni, Amit; Sahariya, Jagrati; Bhamu, K. C.; Ahuja, Ushma (2018 International Conference and Utility Exhibition on Green Energy for Sustainable Development (ICUE), 2018)
In this paper, electronic and optical properties of Cs2PdCl2Br4 perovskite compound are presented using full potential linearized augmented plane wave (FP-LAPW) method. All computations are performed using most accurate modified Becke Johnson (mBJ) potential within density functional theory. Energy band computations are performed over here to elaborate relationship between energy and wave vector (k). Pattern of occurrence observed for energy bands are analyzed in terms of plotted total and partial density of states. For investigating optical behavior of Cs2PdCl2Br4, we have computed dielectric tensor, absorption spectra, reflectivity and refraction spectra using mBJ potential. Different peaks recorded in the imaginary components of dielectric tensor are interpreted in terms of interband transitions for better understanding. Significant absorption intensity available in desired energy range and suitable band gap indicates effective utilization of this compound in photovoltaic applications.

Revealing optoelectronic and transport properties of potential perovskites Cs2PdX6 (X = Cl, Br): A probe from density functional theory (DFT) - Bhamu, K. C.; Soni, Amit; Sahariya, Jagrati (Solar Energy, 2018)
Metal-halide perovskites are rapidly emerging crystalline materials that are reasonably preferred as leading aspirant for applications in optoelectronic and thermoelectric devices. In this paper, we have thoroughly reviewed and performed calculations to reveal optoelectronic and transport properties for a potential newcomer, Cs2PdX6 (X = Cl, Br) termed as Cesium Palladium Halides (CPH). Outcome of present computations are compared with available results and a reasonable agreement is recorded. Energy band gap computations performed reveal indirect band gap of 2.29 eV for Cs2PdC16, which substantially reduces to 1.22 eV when `Cl' is replaced by `Br'. Optical absorption spectra investigations performed here, in the energy range from 3 to 5 eV confirms effective utilization of these compounds in solar cells and other optoelectronic applications. In addition, the transport properties computations performed using semi-classical Boltzmann theory, shows constant pattern of thereto power near ambient temperature range (200-500 K), which admits possible utilization of these compounds as low temperature thermoelectric materials. Performed ZT calculations demonstrates reasonably good thermoelectric performance for both materials, as there exist minor variation (0.1) in the values over wide temperature ranges i.e. from 100 to 800 K. Further, detailed analysis of transport properties predicts p-type semiconducting nature of the present series of materials.
Keywords: Ab-initio studies; Density functional theory; Optical properties; Transport properties

Investigating effect of strain on electronic and optical properties of lead free double perovskite Cs2AgInCl6 solar cell compound: A first principle calculation - Soni, Amit; Bhamu, K. C.; Sahariya, Jagrati (Journal of Alloys and Compounds, 2020)
Despite serious problems associated with toxicity of lead, lead halide perovskite based solar cells have resulted with remarkable efficiency and hence gained much interest. To overcome this aspect, numerous solutions are attempted by researchers which include the development of new environmental friendly lead free double perovskite (DP) photovoltaic materials. Enlightening on the same line, we report first principle calculations on electronic and optical properties of Cs2AgInCl6 solar photovoltaic materials. Present opto-electronic computations for lead free DP compound, have been performed using the full potential linearized augmented plane wave method. In present investigations, we have adopted exchange and correlation potentials prescribed by Perdew et al. and the most accurate Tran-Blaha modified Becke-Johnson. Both exchange and correlation potential computations are performed with and without spin orbit coupling. Results obtained for electronic and optical properties are validated by systematic comparison with available experimental data. Reasonable reconciliation between investigated results and the available experimental data, endorse accuracy of present computations. To identify the effect of strain on energy gap and hence on the optical properties of Cs2AgInCl6 compound, computations of electronic and optical properties have also been performed under the different values of strain application. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Density functional theory; Electronic Structure; Optical properties; solar cells